Technical design and concept of a 0.35 T MR-linac - Klüter, Sebastian (Clinical and translational radiation oncology, 2019)
The integration of magnetic resonance (MR) imaging and linear accelerators into hybrid treatment systems has made MR-guided radiation therapy a clinical reality. This work summarizes the technical design of a 0.35 T MR-Linac and corresponding clinical concepts. The system facilitates 3D-conformal as well as IMRT treatments with 6MV photons. Daily MR imaging provides superior soft-tissue contrast for patient setup and also enables on-table adaption of treatment plans, which is fully integrated into the treatment workflow of the system. Automated beam gating during delivery is facilitated by cine MR imaging and structure tracking. Combining different novel features compared to conventional image-guided radiotherapy, this technology offers the potential for margin reduction as well as dose escalation.